Pengaruh Model Pembelajaran Berbasis Masalah dengan Bantuan Diagram Vee terhadap Kemampuan Berpikir Kritis Mahasiswa Calon Guru Biologi - Chaidir, Diki Muhamad (Quagga : Jurnal Pendidikan dan Biologi, 2018)
The aim of this research is to know the influence of problem-based learning model with the help of vee diagram to critical thinking skill of prospective biology teacher. The research method used is quasi experiment with research design used the matching only pretest-posttest control group design. Population in this research is student of prospective in biology education program, faculty of teacher training and education, Universitas Siliwangi academic year 2016/2017 which contracted courses plant ecology. Sampling technique is done by using purposive sampling as much 2 class, the basic sampling seen from characteristic class that have the same activity. The conclusion of this research is the influence of the use of problem-based learning model with the help of vee diagram to critical thinking skill of prospective biology teacher, it is seen in experimental class have different result of critical thinking skill of prospective biology teacher with control class whose learning process using learning model directly. Problem-based learning models with the help of Vee diagrams have better N-Gain averages compared to direct learning models for critical thinking skills of prospective biology teacher